A system composed of a biofilm electrode reactor and a microbial fuel cell-constructed wetland exhibited efficient sulfamethoxazole removal but induced sul genes. (May 2018) - Zhang, Shuai; Song, Hai-Liang; Yang, Xiao-Li; Li, Hua; Wang, Ya-Wen
Highlights: Excellent SMX removal was acquired by stacked MFC-CW coupled BER. Sul genes in the media and effluent of BER increased with high concentrations of SMX. Sul genes in the media and effluent of BER increased with a decrease in HRT. No obvious variations for the sul genes in the effluent of MFC-CW. No difference between the effects of direct voltage and bioelectricity on sul genes in BER. Abstract: The aim of this work was to study sulfamethoxazole (SMX) removal efficiency and fate of corresponding sul genes in a stacked microbial fuel cell-constructed wetland coupled biofilm electrode reactor system (MFC-CW-BER). Findings showed that two stacked MFC-CWs could provide a relatively stable electricity supply to support the biofilm for SMX removal. Excellent SMX removal (>99.29%) was obtained in the BER-MFC-CW. Compared with the 2000 µg L −1 SMX influent, the relative abundance of the sul genes in biofilm media and effluent was enhanced with continuously high concentrations of SMX (4000 μg L −1 ). The relative abundances of sul genes in biofilm media and effluent increased as the hydraulic retention time decreased. However, there was no obvious variation in the relative abundance of sul genes in the effluent from MFC-CWs. No effect could be observe of the direct voltage and bioelectricity on the relative abundance of the sul genes in the BER.